Dispute Resolution in Islamic Economics: A Comparative Study of Dispute Settlement Mechanisms in Indonesia and Malaysia - Dinta Kharisma Almeira; Chetrine Alya Rinaima; Athia Nur Kamilah (Cv. Kayaswara, 2026)
This article provides a comprehensive comparative analysis of Islamic economic dispute resolution mechanisms in Indonesia and Malaysia, two of the largest Muslim-majority nations in Southeast Asia with rapidly expanding Islamic finance sectors. Employing a normative-juridical approach complemented by comparative legal methodology, this study examines the legislative frameworks, institutional architectures, and procedural modalities governing the settlement of Sharia economic disputes in both jurisdictions. The findings reveal that Indonesia adopts a dual-track system wherein the Religious Courts (Pengadilan Agama) exercise primary adjudicatory jurisdiction over Sharia economic disputes following the enactment of Law No. 3 of 2006, while the National Sharia Arbitration Board (Basyarnas) provides alternative dispute resolution services. Malaysia, by contrast, has developed an integrated framework anchored in the Shariah Advisory Council (SAC) of Bank Negara Malaysia, whose rulings possess binding authority over all courts and arbitral tribunals adjudicating Islamic financial matters. The comparative analysis demonstrates that each jurisdiction has developed contextually appropriate mechanisms shaped by distinct constitutional arrangements, colonial legacies, and legal traditions. This article proposes a harmonization framework that leverages the institutional strengths of both systems, offering policy recommendations for enhancing legal certainty, procedural efficiency, and Sharia compliance in Islamic economic dispute resolution across the ASEAN region